2016
DOI: 10.1159/000446184
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol versus Carvedilol or Metoprolol in Patients Presenting with Acute Myocardial Infarction Complicated by Left Ventricular Dysfunction

Abstract: Objective: The aim of this study was to evaluate the efficacy of nebivolol, carvedilol or metoprolol succinate on the outcome of patients presenting with acute myocardial infarction (AMI) complicated by left ventricular dysfunction. Subjects and Methods: Patients (n = 172, aged 28-87 years) with AMI and left ventricular ejection fraction ≤0.45 were randomized to the nebivolol (n = 55), carvedilol (n = 60) and metoprolol succinate (n = 57) groups. Baseline demographic and clinical characteristics and composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…ECG ST segment elevation was significantly lower after randomisation to nebivolol vs. atenolol, in patients with documented CHD in patients undergoing exercise testing within a randomised trial [ 92 ]. A one-year randomised trial evaluated nebivolol in comparison with metoprolol and carvedilol in 172 patients with acute MI complicated by left ventricular dysfunction [ 93 ]. A composite outcome of nonfatal MI, cardiovascular death, hospitalisation for unstable angina pectoris or heart failure, stroke or revascularisation was significantly lower in the nebivolol vs. metoprolol groups (14.5 vs. 31.5%; p = 0.03), with no significant (p > 0.05) trends for benefit with for nebivolol vs. carvedilol (14.5 vs. 20.3%) and carvedilol vs. metoprolol (20.3 vs. 31.5%, p > 0.05).…”
Section: Bisoprolol and Nebivolol In Ischaemic Heart Diseasementioning
confidence: 99%
“…ECG ST segment elevation was significantly lower after randomisation to nebivolol vs. atenolol, in patients with documented CHD in patients undergoing exercise testing within a randomised trial [ 92 ]. A one-year randomised trial evaluated nebivolol in comparison with metoprolol and carvedilol in 172 patients with acute MI complicated by left ventricular dysfunction [ 93 ]. A composite outcome of nonfatal MI, cardiovascular death, hospitalisation for unstable angina pectoris or heart failure, stroke or revascularisation was significantly lower in the nebivolol vs. metoprolol groups (14.5 vs. 31.5%; p = 0.03), with no significant (p > 0.05) trends for benefit with for nebivolol vs. carvedilol (14.5 vs. 20.3%) and carvedilol vs. metoprolol (20.3 vs. 31.5%, p > 0.05).…”
Section: Bisoprolol and Nebivolol In Ischaemic Heart Diseasementioning
confidence: 99%
“…W niedawno opublikowanym badaniu randomizowanym porównano skuteczność nebiwololu, karwedylolu oraz bursztynianu metoprololu u pacjentów zgłaszających się z powodu ostrego MI powikłanego dysfunkcją lewej komory (LVEF ≤ 45%) [25]. Losowo przydzielono pacjentów (n = 172, 28-87 lat) do leczenia nebiwololem (n = 55), karwedylolem (n = 60) lub metoprololem (n = 57).…”
Section: Authorunclassified
“…In acute coronary syndromes, a small-scale study showed that patients that had an infarction with ventricular dysfunction had fewer events (infarction/death/hospitalization due to coronary syndrome/ stroke or need of revascularization) over 12 months than those patients treated with Metoprolol and similar to those treated with Carvedilol [73].…”
Section: Nebivolol In Cases Of Coronary Diseasementioning
confidence: 99%